The impact of severity of disability of stroke on tme quality of life of home-based family caregivers in Kelantan - Fatin Nazihah, Muhammed (Universiti Sains Malaysia, 2009)
This study examined the impact of severity of stroke disability on the quality of life (Qol) of home-based family caregivers in Kelantan. This study also examined the association between demographic characteristics of family caregivers with their quality of life. A random sample of caregivers (n=37) completed two questionnaires. Barthel Index (81) was used to evaluate disability severity in stroke patients. Bakas Caregiving Outcomes Scale (BCOS) was applied to evaluate the quality of life among caregivers. On the 81, 37.8% (n=14) scored 0-59, indicating they were dependent. The BCOS with mean of 59.08 (80=9.12), indicating overall slight change for the worst. There is no association between demographic characteristics regarding age, sex, race, marital status and educational level with family caregivers' quality of life. But, there is an association between family caregivers' job, total monthly income and caregiving duration with their quality of life. The correlation between disabilities in stroke patients and quality of life in their caregivers was determined in statistical analysis between Bl and BCOS. There is a significant moderate relationship between Bl total score and BCOS total score (r-0.645, p<0.001 ). Interventions aimed at improving the quality of life of family caregivers need further exploration.